Comparing 5G hybrid beamforming in indoor environments—collocated vs distributed mmWave arrays - Bagheri, Alireza; Bencivenni, Carlo; Glazunov, Andrés Alayón (Frontiers in Communications and Networks, 2024)
This paper studies the performance of hybrid digital-analog multi-user multiple-input multipleoutput (MU-MIMO) downlink communication based on various antenna systems for 5G applications. The analysis is focused on comprehensive numerical simulations comparing hybrid beamforming schemes for collocated vs. distributed phased array antennas (PAA) deployments in two indoor office environments. This study uses measured beamforming radiation patterns from two 28 GHz state-of-the-art PAAs. The channel models employed are the standardized statistical 3GPP 38.901 indoor channel models implemented in the QuaDRiGa software. A beam selection algorithm is implemented to maximize the achievable sum rate, assuming either matched-filtering or zero-forcing precoding. The evaluated figures of merit are the gain of the RF power amplifier, the per-user signal-to-interference-plus-noise ratio (SINR), and the resulting achievable sum-rate capacity. Based on the results, the distributed deployment scenario always shows a higher SINR and achievable sum-rate capacity at the user locations while requiring a lesser amplification of the conducted power. Specifically, the largest PAA with slant-polarized 16 × 4 elements producing 16 horizontal analog beams in combination with zero-forcing digital precoding proved to be the best solution in both open and mixed indoor office environments in absolute values. On the other hand, the array based on the same type of elements but in a more compact realization with 4 × 4 elements, but with beams arranged as 8 horizontal times 2 vertical, offered the most significant relative gains.